THE APPLICATION OF THE CONCEPT OF AUDITORY PERCEPTION TO THE SPACE-FORM OF CALVINIST CHURCH : GKI PENGAMPON, CIREBON CITY: PENERAPAN KONSEP PERSEPSI AUDITORI PADA RUANG-BENTUK GEREJA KRISTEN CALVINIS : GKI PENGAMPON, KOTA CIREBON - Indri Astrina Wirakusumah; Joshua Nathanael Jogia; Purnama Salura (Universitas Telkom, 2025)
Abstract : Modern church architecture often emphasizes visual aesthetics, frequently overlooking to the crucial auditory dimension essential to shaping a sacred worship experience. Within the Christian tradition, particularly in Calvinist churches, auditory perception plays a significant role in facilitating divine communication during liturgy. This study investigates the` relationship between auditory perception and spatial form in Christian church architecture, using GKI Pengampon Church in Cirebon as a case study. Employing a qualitative methodology, the research involves: (1) a theoretical exploration of church architecture and auditory perception; (2) spatial mapping of the main worship space at GKI pengampon; (3) formulation of ideogram standards for auditory perception in relation to architectural form and space; (4) comparative analysis between the case study and theoretical perceptual standards; and (5) synthesis of findings. The aim is to elucidate the interplay between auditory perception and spatial form in the context of Calvinist worship. The findings reveal that, while the church exhibits visual elements aligned with Calvinist architectural principles, its spatial configuration does not adequately support acoustic quality or congregational auditory experience. This research contributes to the theoretical discourse on multisensory architecture and offers practical insights for designing worship spaces that holistically address the spiritual and sensory needs of the congregation. Keyword : architecture, christian church, liturgy, auditory perception